MAL KREATIF TANAH ABANG: PERANCANGAN, PENCIPTAAN, DAN PEMASARAN DALAM SATU BANGUNAN - William Jaya Saputra (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The world is developing rapidly influencing the culture of society. In this decade, the driving force of civilization was dominated by millennials who were known for their freedom, convenience, innovation and digitalization. Apart from the common old professions, millennials have the freedom to do professions that are in accordance with their passion. Fashion and craft are the most interested one by millennials. Many of them are fresh entrepreneurs that use their hobbies and passions such as becoming influencers and designing, and selling it by themselves or in groups following the trends of outfit of the day and so on through the digital world. The purpose is to bring pride when the results of ideas, works, and innovations that are owned and recognized by others. The desire of millennial entrepreneurs is the convenience and comfort of work, such as designing, creating, and marketing their work in one integrated place. Therefore, a forum for millennials & others is needed to express innovative ideas, produce works, and at the same time be able to showcase and sell their works. AbstrakDunia berkembang pesat memengaruhi kultur budaya masyarakat. Di dekade ini, motor penggerak peradaban didominasi oleh kaum milenial yang terkenal akan kebebasan, kemudahan, inovasi, dan digitalisasinya. Terlepas dari profesi-profesi lawas yang umum, milenial memiliki kebebasan untuk menjalankan profesi yang sesuai dengan passion mereka. Fesyen dan kriya merupakan salah dua bidang yang paling diminati kaum milenial. Banyak dari mereka yang berwirausaha dini dengan memanfaatkan hobi dan passion mereka seperti menjadi influencer dan mendesain dan menjualnya sendiri atau berkelompok mengikuti tren outfit of the day dan sebagainya melalui dunia digital. Tujuannya adalah untuk memunculkan rasa bangga ketika hasil ide, karya, dan inovasi yang dimiliki diakui dan dinikmati orang lain. Keinginan wirausahawan milenial adalah kemudahan dan kenyamanan dalam bekerja, seperti merancang, menciptakan, dan memasarkan hasil karya mereka dalam satu tempat terpadu. Oleh karena itu, dibutuhkan wadah bagi kaum milenial & lainnya untuk menuangkan ide-ide inovatif, menghasilkan karya, dan sekaligus dapat memamerkan dan menjual karya mereka.